PERANCANGAN VISI ARSITEKTUR TOGAF PADA INSTITUSI PENDIDIKAN TINGGI STUDI KASUS: UNIVERSITAS BUNG KARNO - Sudirman Sudirman (STIKOM CKI, 2017)
Nowadays, organizations must fulfill themselfes to develop series of Information Technology trough various of Information Systems, the purposes is to attend the continuity of business process and to face the competition. On the contrary, the complexity of existing information systems and the interface has created the complexity of Information Technology landscape/architecture. The purpose of this research is to find a gap in a way to anticipate the complexity described above, by taking a case study at University Of Bung Karno, Jakarta. TOGAF is an Information Technology/Information System (IS/IT) Architecture Framework that is used in this research. The output of research is steps of architecture vision that will be used as inputs for the next steps such as Business Architecture, Information System Architecture and Technology Architecture.Keywords: Information Technology/ Information System, TOGAF, Architecture Vision